Studies on Schismatoglottideae (Araceae) of Borneo XXXX: Schismatoglottis petradoxa and S. tseui, new shale-obligate rheophytes of uncertain affinity - Wong, Sin Yeng; Boyce, P.C (International Aroid Society, Inc., 2014)
Two taxonomically new rheophytic species of Schismatoglottis of uncertain affinity, S. petradoxa S. Y. Wong & P. C. Boyce sp. nov. and S. tseui S. Y. Wong & P. C. Boyce sp. nov., are described and illustrated from forested shale waterfalls in central North Borneo.